Total hip arthroplasty for tuberculous coxitis. - Caparros, A. B. (Springer-Verlag, 1999)
We report a case of tuberculous arthritis of the hip in a 22 year old male patient, treated with arthrotomy and antituberculous antibiotic therapy for 9 months; the joint deteriorated and 2 years later he underwent uncemented total hip arthroplasty. He received antibiotic therapy for 3 months preoperatively and for 6 months postoperatively. At 5 year follow-up there was no evidence of recurrent infection.